Impact of Nutrition in the Management of Nutritional Status of Covid-19 Patients - Soni, Shashi; Noor, Uroosa; Gupta, Ena (Current Nutrition & Food Science, 2022)
Abstract: The second outbreak of severe acute respiratory syndrome coronavirus (SARS-CoV-2) is of great concern due to its awful mortality and morbidity rate with decreasing nutritional status and poor lifestyle as well as noteworthy food crisis and affected economy of the world. Increasing food prices, food crisis, global hunger and decreasing availability and feasibility of food are the foremost causes of decreasing nutritional status, which increases the risk of susceptibility to infection and, in turn, leads to unfavorable outcomes of the diseases. Although, in times of the Covid- 19 pandemic, nutrition is of potential attention, and there is a requirement for more exploration in the field of nutrition for the prevention of diseases arising from coronavirus infection. Elderly and individuals with co-morbidity, such as respiratory diseases, cardiovascular diseases, diabetes mellitus and metabolic diseases, are more prone towards getting infected with the coronavirus. Good nutrition is mandatory for healthy immune responses, which can be improved by the inclusion of vitamin A, B6, B12, C, D, E, zinc, selenium, iron, copper and an antioxidant-rich diet.
Keywords: immune response